Peningkatan Hasil Belajar Kesehatan Pribadi Melalui Model Pembelajaran Koperasi Tipe Jigsaw Untuk Siswa Kelas V SD Negeri Telaga Pange - Safianti, Wa Ode; Unmehopa, Wilhelmina (MANGGUREBE: Journal Physical Education, Health and Recreation, 2024)
Health is the most valuable asset, the expression is said when the person has fallen ill. Healthy at least a person is very dependent on the behavior of the person's daily life. Therefore, everyone needs to be given information about health so that they can lead a life in accordance with health principles. Health aims to improve people's standard of living optimally. In order to achieve this goal, the community is encouraged to know the problems and find ways to overcome the various problems that arise. So far, health development has focused more on efforts to cure diseases, so that the focus of government attention has been directed more towards the development of health facilities such as health centers and hospitals. Soekamto, et al in Titu, (2015) stated the purpose of the learning model is "a conceptual framework that describes a systematic procedure for organizing learning experiences to achieve certain learning goals, and serves as a guide for learning designers and teachers in planning learning activities." The jigsaw type cooperative learning model can improve personal health learning outcomes in fifth grade students of Talaga Pange Public Elementary School. Through the application of the jigsaw type cooperative method, it can improve personal health learning outcomes. -the average achievement of the results obtained by the subject or student.